Impaired serine metabolism complements LRRK2-G2019S pathogenicity in PD patients. (October 2019) - Nickels, Sarah Louise; Walter, Jonas; Bolognin, Silvia; Gérard, Deborah; Jaeger, Christian; Qing, Xiaobing; Tisserand, Johan; Jarazo, Javier; Hemmer, Kathrin; Harms, Amy; Halder, Rashi; Lucarelli, Philippe; et al.
Abstract: Parkinson's disease (PD) is a multifactorial disorder with complex etiology. The most prevalent PD associated mutation, LRRK2-G2019S is linked to familial and sporadic cases. Based on the multitude of genetic predispositions in PD and the incomplete penetrance of LRRK2-G2019S, we hypothesize that modifiers in the patients' genetic background act as susceptibility factors for developing PD. To assess LRRK2-G2019S modifiers, we used human induced pluripotent stem cell-derived neuroepithelial stem cells (NESCs). Isogenic controls distinguish between LRRK2-G2019S dependent and independent cellular phenotypes. LRRK2-G2019S patient and healthy mutagenized lines showed altered NESC self-renewal and viability, as well as impaired serine metabolism. In patient cells, phenotypes were only partly LRRK2-G2019S dependent, suggesting a significant contribution of the genetic background. In this context we identified the gene serine racemase ( SRR ) as a novel patient-specific, developmental, genetic modifier contributing to the aberrant phenotypes. Its enzymatic product, d -serine, rescued altered cellular phenotypes. Susceptibility factors in the genetic background, such as SRR, could be new targets for early PD diagnosis and treatment. Highlights: Stem cells from LRRK2-G2019S patients show impaired self-renewal, viability, and serine metabolism. Patient phenotypes only partly depend on LRRK2-G2019S, the PD genetic background contributes. Identification of SRR as a possible susceptibility factor within the PD genetic background. The enzymatic product of SRR, D-serine rescues background related phenotypes within PD patient cells.